Efficacy and safety of Wuhu oral liquid in treating acute soft tissue injuries: a multicenter, randomized, double-blind, double-dummy, parallel-controlled trial - Zhu, Wen-Hao; Shen, Yi; Xiao, Yu; Shi, Qi; Fan, Zhao-Xiang; Feng, Yan-Qi; Wan, Hong-Bo; Qu, Bo; Zhao, Jun; Zhang, Wei-Qiang; Xu, Guo-Hui; Wu, Xue-Qun; et al. (Frontiers in Pharmacology, 2024)
Background: Wuhu Oral Liquid (WHOL) is a modified preparation derived from the famous Wuhu Powder, which has a long history of use in treating traumatic injuries. This preparation has anti-inflammatory and analgesic properties and accelerates recovery following acute soft tissue injuries. Aims: To evaluate the efficacy and safety of WHOL in treating acute soft tissue injury associated with qi stagnation and blood stasis syndrome and to provide a basis for applying for the protection of varieties of Chinese medicine for WHOL. Methods: This study was a randomized, controlled, double-blind, multicenter clinical trial in which Fufang Shang Tong Capsule (FFSTC) was selected as the control drug. A total of 480 subjects with acute soft tissue injury associated with qi stagnation and blood stasis syndrome were randomly divided into a test and control group in a 3:1 ratio. The duration of drug treatment was 10 days. The primary outcome was Visual Analogue Scale (VAS) score for pain (including pain at rest and pain on activity). Secondary outcomes included the disappearance time of the pain at rest and on activity; the curative effect of TCM syndrome and improvement in the individual symptoms of TCM (swelling, ecchymosis, and dysfunction); and changes in C-reactive protein (CRP) and interleukin-6 (IL-6) levels. Safety was assessed using vital signs, laboratory examinations, electrocardiograms, and physical examinations. Results: Patient compliance was satisfactory in both groups (all between 80% and 120%). After 4 days of treatment, the WHOL group was superior to the FFSTC group in decreasing the VAS scores for pain at rest (−1.88 ± 1.13 vs. −1.60 ± 0.93, p < 0.05) and on activity (−2.16 ± 1.18 vs. −1.80 ± 1.07, p < 0.05). After 7 days of treatment, the WHOL group was superior to the FFSTC group in decreasing the VAS scores for pain on activity (−3.87 ± 1.60 vs. −3.35 ± 1.30, p < 0.01) and improving swelling (cure rate: 60.4% vs. 46.2%, p < 0.05; obvious effective rate: 60.7% vs. 47.0%, p < 0.05). After 10 days of treatment, the WHOL group was superior to the FFSTC group in decreasing the levels of CRP (−0.13 ± 2.85 vs. 0.25 ± 2.09, p < 0.05) and improving the TCM syndrome (cure rate: 44.1% vs. 30.8%, p < 0.05) and swelling (cure rate: 75.6% vs. 67.5%, p < 0.01; obvious effective rate: 75.6% vs. 68.4%, p < 0.05; effective rate: 77.0% vs. 71.8%, p < 0.05). The disappearance time of pain at rest was 8 days in both groups and 9 days on activity in both groups. In addition, there was no statistical difference between the incidence of adverse events (4.5% vs. 2.6%, p > 0.05) and adverse reactions (0.3% vs. 0%, p > 0.05) between the WHOL group and the FFSTC group. No serious adverse events occurred in either group, and no subjects were withdrawn because of adverse events. Conclusion: WHOL relieves the symptoms caused by acute soft tissue injury associated with qi stagnation and blood stasis syndrome more rapidly than FFSTC, and it is effective and safe in the treatment of acute soft tissue injury. Future studies still need a larger sample size to verify its efficacy and safety. Clinical Trial Registration:https://www.chictr.org.cn/showproj.html?proj=149531, Identifier ChiCTR2200056411.